2020
DOI: 10.1021/acsami.0c19330
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of FeOCl in Hollow Dendritic Mesoporous Organosilicon for Ascorbic Acid-Enhanced and MR Imaging-Guided Chemodynamic Therapy in Neutral pH Conditions

Abstract: Chemodynamic therapy (CDT) based on the Fenton reaction is a promising strategy for nonlight cancer treatment. However, the traditional Fenton reaction is only efficient in strongly acidic conditions (pH = 2−4), resulting in the limited curative effect in a weakly acidic tumor microenvironment (TME). Herein, we first developed a simple in situ growth method to confine FeOCl nanosheets into hollow dendritic mesoporous organosilicon (H-DMOS) nanoparticles to obtain FeOCl@H-DMOS nanospheres. Ascorbic acid (AA) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…One method is to enhance the conversion efficiency between Fe 2+ and ferric ions (Fe 3+ ). [ 27–31 ] For example, to deal with the contradiction between acidic environment‐dependent CDT and the neutral pH condition at the tumor surface, [ 32 ] Zhao et al. synthesized a type of chelating complex ferrous‐cysteine–phosphotungstate nanoparticles (FcPWNPs) to improve the CDT efficiency by introducing cysteine and phosphotungstate ( Figure a).…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
“…One method is to enhance the conversion efficiency between Fe 2+ and ferric ions (Fe 3+ ). [ 27–31 ] For example, to deal with the contradiction between acidic environment‐dependent CDT and the neutral pH condition at the tumor surface, [ 32 ] Zhao et al. synthesized a type of chelating complex ferrous‐cysteine–phosphotungstate nanoparticles (FcPWNPs) to improve the CDT efficiency by introducing cysteine and phosphotungstate ( Figure a).…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
“…[34,46,47] In general, it was the overexpression of superoxide dismutase in the tumor region that converted superoxide negative ions produced by the mitochondria of tumor cells into H 2 O 2 . [48] Since H 2 O 2 was one of the necessary reactants of CDT, the low concentration level in normal tissue cells was inadequate to cause destructive Fenton or Fenton-like reactions, providing CDT with high selectivity. [49] The typical Fenton reaction was derived from iron-based nanomaterials, of which the optimal pH was between 2.0 and 4.0.…”
Section: The Mechanism For the Bioimaging Including Mri And Cancer Treatment Based On The Mn-based Nanostructuresmentioning
confidence: 99%
“…synthesized FeOCl@H‐DMOS‐AA/PEG for the intracellular production of ROS by catalyzing H 2 O 2 with the help of ascorbic acid. [ 8 ] According to their MTT results, a high concentration of H 2 O 2 (0.6 × 10 −3 m ) could trigger the cytotoxicity of the nanoparticles. In our study, however, by adding 100 × 10 −6 m H 2 O 2 to the culture medium, we observed higher cytotoxicity at an almost equal concentration of the nanoparticle.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the nanocomposites of FeOCl have been employed for tumor chemodynamic therapy (CDT). [ 8,9 ] In CDT, the acidity and overproduction of hydrogen peroxide in the tumor microenvironment favors the progression of the Fenton reaction. [ 10,11 ] In the presence of a Fenton or Fenton‐like reagent, hydroxyl radicals generate from the decomposition of hydrogen peroxide, which ultimately induces in situ toxicity to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation